2016
DOI: 10.1007/s00247-016-3619-6
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal brain MRI of fetuses with Zika virus infection

Abstract: Results Three out of 12 cases of severe cerebral lesions fulfilled all inclusion criteria. History of maternal Zika virus infection had been documented in two cases. Calcifications and ventriculomegaly were present at US in all cases. MRI showed micrencephaly (n = 3), low cerebellar biometry (n = 2), occipital subependymal pseudocysts (n = 2), polymicrogyria with laminar necrosis and opercular dysplasia (n = 3), absent (n = 1) or hypoplastic (n = 1) corpus callosum and hypoplastic brainstem (n = 1). Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…Besides the similar pattern of distribution of calcifications described here, malformation of cortical development with predominance of pachygyria or polymicrogyriain the frontal lobes and delayed myelination were seen. As well, Guillemette-Arturet al 25 recently reported very similar findings in a three-patient series using fetal MRI, including subependymal pseudocysts.…”
Section: Discussionsupporting
confidence: 63%
“…Besides the similar pattern of distribution of calcifications described here, malformation of cortical development with predominance of pachygyria or polymicrogyriain the frontal lobes and delayed myelination were seen. As well, Guillemette-Arturet al 25 recently reported very similar findings in a three-patient series using fetal MRI, including subependymal pseudocysts.…”
Section: Discussionsupporting
confidence: 63%
“…Twenty-eight items [29, 30, 34, 3638, 40, 41, 44, 51, 52, 54–58, 61, 63, 64, 67, 69, 72, 75, 77, 79, 81, 85, 91–93] in 25 groups addressed biological plausibility (S4 Table). These studies suggest a teratogenic effect of Zika virus on the developing brain.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that HSV-1 receptors are expressed at only low levels in gestation, but rise markedly during the postnatal period, is notable because the fetal human brain is not generally subject to infection with HSV-1, in contrast to other viruses (e.g., cytomegalovirus, rubella, Zika virus) that can establish damaging brain infection during gestation (Driggers et al 2016; Guillemette-Artur et al 2016; McCarthy et al 2011; Naeye and Blanc 1965). Although exposed to HSV-1 in utero of HSV-1-positive mothers, overt pathology appears to be generally limited to postnatal ages.…”
Section: Discussionmentioning
confidence: 99%